The optimisation of cruciform specimen for the formability evaluation of AA6082 under hot stamping conditions - Shao,Z; Li,N; Lin,J (Procedia Engineering, 2017)
The hot stamping and cold die quenching process is increasingly adopted to form complex-shaped structures of sheet metals in the automotive industry. However, it is difficult to obtain formability data of sheet metals under hot stamping conditions by using conventional experimental testing methods. In this study, a novel in-plane biaxial testing system, which is attached to a Gleeble materials thermo-mechanical simulator, had been developed for determining forming limit diagrams (FLDs) under hot stamping conditions. However, there is no standard of cruciform specimen geometries available for this type of biaxial tests. In this paper, the features of thickness reduction in the central region and slots in the arms of a type of cruciform specimen of aluminium alloy 6082 were verified first to increase strain uniformity of the biaxial loading zone on a cruciform specimen, based on the selective heating and cooling method. Finite Element (FE) thermo-electrical and thermo-mechanical models with UAMP and VUMAT subroutines were then implemented in ABAQUS 6.12 to optimise specimen dimensions so that fracture occurs in the concerned central region of the specimen during testing. By the use of the optimised specimen for AA6082 in the biaxial testing system, formability tests under the designated strain paths were conducted at specified hot stamping conditions. Strain fields in the gauge region of the cruciform specimens were measured using the digital image correlation (DIC) system and the experimental results were presented and analysed in order to verify the cruciform specimen design.